2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6611151
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of visual space recognition in patients with visual field defects using head mounted display (HMD) system: Case study with severe visual field defect

Abstract: For the quantitative assessment of visual field defects of cerebrovascular patients, we developed a new measurement system that could present various kinds of visual information to the patient. In this system, we use a head mounted display as the display device. The quantitative assessment becomes possible by adding the capability to measure the eye movement and the head movement simultaneously by means of a video apparatus of motion analysis. In our study, we examined the effectiveness of this system by apply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Since the CBS results of USN patients who participated in this study indicated left neglect in ADL, it is plausible, as previously reported by Tanaka et al [17][18][19][20] that this HMD system featuring diverse visual indexes could discern USN symptoms that otherwise would not have been detected through conventional desktop tests. Furthermore, correct response rates were found to be lower for the right side of the sheet (i.e., the unimpaired side) in VFD and USN patients.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Since the CBS results of USN patients who participated in this study indicated left neglect in ADL, it is plausible, as previously reported by Tanaka et al [17][18][19][20] that this HMD system featuring diverse visual indexes could discern USN symptoms that otherwise would not have been detected through conventional desktop tests. Furthermore, correct response rates were found to be lower for the right side of the sheet (i.e., the unimpaired side) in VFD and USN patients.…”
Section: Discussionsupporting
confidence: 65%
“…Moreover, USN symptoms not disclosed by the ordinary line cancellation test were found by the HMD system. Eyes and head movement analysis were also added to our HMD system [19,20]. Various reports have described the assessment of the eye movement of left USN patients [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The USN patients in this laboratory test presented left spatial neglect in the everyday life according to the CBS score. A new assessment and training for USN with use of a HMD was proposed by Tanaka et al 19 , 20 , 21 ) . There are a few reasons for the decline in the line cancellation rate for the right sheet of the VFD and USN patients.…”
Section: Discussionmentioning
confidence: 99%
“…USN symptoms not disclosed by the ordinary line cancellation test were found by the HMD system. Eyes and head movement analysis were also added to the HMD system 20 , 21 ) .…”
Section: Introductionmentioning
confidence: 99%